Sintesis Silika dari Abu Terbang (Fly Ash) Batubara PT YTL Paiton secara Batch - Diana Novita Sari; Nadya Rizkita; Aulia Firda Alfiana; Theresia Dea Randha Rosalina (Ekliptika, 2024)
Fly ash, as waste from burning coal, contains dominant amounts of silica (SiO2), so it can be used as a source of silica. Silica synthesis can be done by reacting fly ash with an alkaline solution and precipitating the silica with an acidic solution. In this research, the variables used are the type of reactant, process temperature and the mass ratio of the raw material to the reactant, with the aim of knowing the silica yield produced. Silica synthesis was carried out using 3M NaOH and KOH with variations in temperature (75, 85, 95, 105 oC), mole ratio of fly ash to NaOH (1:10.09; 1:12.61; 1:15.13) and KOH ( 1:7.34; 1:9.17). The initial fly ash content was carried out by XRF analysis and the silica resulting from the extraction process was calculated by % yield and SEM analysis. The research shows that the highest % yield at a temperature of 950C and mole ratio of 1:15.13 is 105.6% using NaOH solvent and a raw material: reactant ratio of 1:11 of 1.184 grams with yield of 43.05% using KOH solvent, Yields that exceed 100% are caused by impurities that are taken in during the silica extraction process. The silica results in both reactant type variables have an average particle size of 36 -77 nm.